2022
DOI: 10.1002/cam4.4688
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidities rather than older age define outcome in adult patients with tumors of the Ewing sarcoma family

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
0
0
0
4
Order By: Relevance
“…As such, our patient's disease was managed through surgical resection alone followed by surveillance, and he has been without evidence of disease for four years. Striefler et al found in their cohort study that comorbidities were more strongly predictive of outcomes rather than older age in adult patients [10]. In children, EES has interestingly been shown to carry a more favorable prognosis than its classic skeletal counterpart [11].…”
Section: Discussionmentioning
confidence: 98%
“…As such, our patient's disease was managed through surgical resection alone followed by surveillance, and he has been without evidence of disease for four years. Striefler et al found in their cohort study that comorbidities were more strongly predictive of outcomes rather than older age in adult patients [10]. In children, EES has interestingly been shown to carry a more favorable prognosis than its classic skeletal counterpart [11].…”
Section: Discussionmentioning
confidence: 98%
“…Наприклад, хронічне обструктивне захворювання легень (ХОЗЛ) є частиною системного запального синдрому та асоціюється з раком легень, остеопорозом, прогресуванням атеросклерозу та хронічною хворобою нирок (ХХН) [11]. У роботах по коморбідності в онкоортопедії зазначено, що загальна смертність вища у хворих на первинні злоякісні новоутворення кісток з коморбідністю, ніж у хворих без коморбідності [15,29]. Коморбідність певною мірою впливає на всю «траєкторію» пухлинного процесу, починаючи з моменту формування передиспозиції до нього аж до встановлення діагнозу, призначення лікування та подальшого моніторингу [13,14,16,17,53,57].…”
Section: вступunclassified
“…Хворі на злоякісні новоутворення кісток у 33-52 % спостережень мають такі поліморбідні хронічні захворювання: остеопороз, артрит, артроз, виразкова хвороба шлунка чи дванадцятипалої кишки, панкреатит, холецистит, облітеруючі захворювання артерій нижніх кінцівок, ішемічну хворобу серця, артеріальну гіпертензію, гострі порушення мозкового кровообігу з мінімальними залишковими явищами, хронічну обструктивну хворобу легень, сахарний діабет ІІ типу [15,29,32].…”
Section: рисунок 1 питома вага онкологічних пацієнтів з коморбідністю...unclassified
See 2 more Smart Citations